The violin conspiracy [large type] - Slocumb, Brendan (Random House Large Print, 2022)
"Ray McMillian loves playing the violin more than anything, and nothing will stop him from pursuing his dream of becoming a professional musician. Not his mother, who thinks he should get a real job, not the fact that he can't afford a high-caliber violin, not the racism inherent in the classical music world. And when he makes the startling discovery that his great-grandfather's fiddle is actually a priceless Stradivarius, his star begins to rise. Then with the international Tchaikovsky Competition-the Olympics of classical music-fast approaching, his prized family heirloom is stolen. Ray is determined to get it back. But now his family and the descendants of the man who once enslaved Ray's great-grandfather are each claiming that the violin belongs to them. With the odds stacked against him and the pressure mounting, will Ray ever see his beloved violin again?"--